2018
DOI: 10.1007/s00294-018-0899-4
|View full text |Cite
|
Sign up to set email alerts
|

Condensin action and compaction

Abstract: Condensin is a multi-subunit protein complex that belongs to the family of structural maintenance of chromosomes (SMC) complexes. Condensins regulate chromosome structure in a wide range of processes including chromosome segregation, gene regulation, DNA repair and recombination.Recent research defined the structural features and molecular activities of condensins, but it is unclear how these activities are connected to the multitude of phenotypes and functions attributed to condensins. In this review, we brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 123 publications
0
31
0
Order By: Relevance
“…The models, which also assume that MukBEF loads randomly on all chromosomal regions, explain how MukBEF clusters colocalize with the replication origin region (oriC) in wild-type cells, while MukBEF clusters localize equally with all genetic regions tested in MatP − cells. (Kakui and Uhlmann 2018;Wani et al 2018;Paul et al 2019;Yatskevich et al 2019) Is the MukBEF-organized E. coli chromosome placed randomly within a cell? Early imaging studies showed that in new-born E. coli cells that have not initiated replication, the left and right replichores are organized into separate cell halves, while oriC is at midcell (Wang et al 2006).…”
Section: Chromosome Organization In E Coli and Other Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The models, which also assume that MukBEF loads randomly on all chromosomal regions, explain how MukBEF clusters colocalize with the replication origin region (oriC) in wild-type cells, while MukBEF clusters localize equally with all genetic regions tested in MatP − cells. (Kakui and Uhlmann 2018;Wani et al 2018;Paul et al 2019;Yatskevich et al 2019) Is the MukBEF-organized E. coli chromosome placed randomly within a cell? Early imaging studies showed that in new-born E. coli cells that have not initiated replication, the left and right replichores are organized into separate cell halves, while oriC is at midcell (Wang et al 2006).…”
Section: Chromosome Organization In E Coli and Other Bacteriamentioning
confidence: 99%
“…Distant relations to the SMC complexes above are Rad50 and RecN, involved in repair of double-strand DNA breaks (not shown). For further details see (Kakui and Uhlmann 2018 ; Wani et al 2018 ; Paul et al 2019 ; Yatskevich et al 2019 ) …”
Section: Overviewmentioning
confidence: 99%
“…The canonical role of condensin is as a molecular motor that extrudes DNA loops thereby organising chromosome architecture during mitotic chromosome compaction [71]. Given that condensin has this ability to rearrange chromosome topologies, it is feasible that the action of Cap-G in neurons could be to remodel 3D chromatin structure for optimal gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…A similar condensinmediated tuning of histone modifications on mitotic chromosomes may be important for proper inheritance of transcriptional programs after cell division. Future work on how the DCC modulates histone modifications and transcriptional activity of gene regulatory elements will be important to cross-reveal mechanisms by which condensin-mediated organization of mitotic chromosomes affect gene regulation across cell division [4].…”
Section: The First Question This Model Raises Is How the DCC Targets mentioning
confidence: 99%
“…Condensins are required for chromosome condensation and segregation in all eukaryotes [3]. Condensins are also important for genome organization and have been implicated in gene regulation during interphase [4]. Genome-wide binding experiments indicate that condensins bind to a subset of gene regulatory elements including promoters, enhancers, tRNA genes, and topologically associated domain (TAD) boundaries [5].…”
Section: Introductionmentioning
confidence: 99%